Some reflections on inflation targeting, monetary–fiscal policy interactions, and unconventional monetary policies - Jean-Luc Gaffard; Mauro Napoletano; Stefano Battiston (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
We revisit the theoretical underpinnings of the monetary policy consensus before the Great Recession. We highlight how they resulted from New Keynesian dynamic stochastic general equilibrium (DSGE) models that (i) neglected the actual process of coordination in markets, (ii) saw price rigidity as an obstacle to the correct functioning of markets, and (iii) overlooked the effects of finance on the determination of credit supply. Furthermore, we outline some elements of an alternative framework conceiving the output-inflation dynamics as the result of coordination efforts in markets that are constantly in disequilibrium. We discuss how such a disequilibrium perspective leads to opposite conclusions with respect to DSGE models about the role of price rigidity and of fiscal and monetary policy interactions, and about the process of endogenous money formation and credit supply. Finally, in such a perspective, quantitative easing policies may play a key role also in normal times as key determinants of the distribution of financial risk.
Keywords: E31; E32; E5; E61; E62; 330; output-inflation dynamics; New Keynesian models; disequilibrium analysis; monetary-fiscal policy interactions; quantitative easing policies